Efficacy and survival analysis of nimotuzumab combined with concurrent chemoradiotherapy in the treatment of locally advanced nasopharyngeal carcinoma - Wang, Lili; Zhuang, Hengzhao; Xu, Xiaoyan; Zhou, Juying; Jiao, Yang (Frontiers in Oncology, 2023)
Objective: This study investigated the curative effect of adding nimotuzumab (NTZ) in patients with locally advanced nasopharyngeal carcinoma (NPC) who were treated with concurrent chemoradiotherapy (CCRT) and explored significant prognostic factors of NPC. Materials and Methods: The clinical data of 307 patients with NPC treated in the First Affiliated Hospital of Soochow University from January 2013 to December 2018 were retrospectively analyzed. The patients were divided into the NTZ-CCRT group and the CCRT group according to whether they were associated with NTZ. We applied propensity score matching to reduce the interference of biases and compared the short-term efficacy and long-term survival rate of the two groups. Moreover, univariate and multivariate analyses were performed for all patients, and subgroup analysis was used to compare the efficacy of therapy combined with NTZ in different subgroups. Results: In primary nasopharyngeal tumors, the objective response rates in the NTZ-CCRT group and CCRT group were 95.8% and 85.7%, respectively (P =0.007). In cervical positive lymph nodes, the objective response rates in the NTZ-CCRT group and CCRT group were 98.3% and 87.4%, respectively (P =0.001). Compared with CCRT alone, the addition of NTZ significantly improved the 5-year OS (94.1% vs. 81.8%, P=0.014) and the 5-year DFS (84.2% vs. 75.5%, P=0.031) of NPC patients; however, the addition of NTZ was accompanied by more severe hematologic toxicity and acute oral mucositis. Multivariate analysis demonstrated that the addition of NTZ was an important prognostic factor for OS and DFS (HR 0.367, 95% CI 0.167-0.808, P=0.013 for OS and HR 0.536, 95% CI 0.312-0.919, P=0.023 for DFS) and the level of pretreatment LDH (HR 5.170, 95% CI 2.125-12.580, P<0.001 for OS and HR 2.421, 95% CI 1.027-5.707, P=0.043 for DFS). Moreover, patients with high levels of hsCRP before treatment (HR 0.389, 95% CI 0.177-0.853, P=0.018) may gain more benefits from combined treatment with NTZ. Conclusions: For locally advanced NPC patients treated with concurrent chemoradiotherapy, the addition of NTZ can significantly improve their survival outcome. However, it is necessary to guard against the associated increase in hematological toxicity and acute oral mucositis.